The impact of large and small dams on malaria transmission in four basins in Africa - Kibret, S.; McCartney, Matthew P.; Lautze, Jonathan F.; Nhamo, Luxon; Yan, G. (Springer, 2021)
Expansion of various types of water infrastructure is critical to water security in Africa. To date, analysis of adverse disease impacts has focused mainly on large dams. The aim of this study was to examine the effect of both small and large dams on malaria in four river basins in sub-Saharan Africa (i.e., the Limpopo, Omo-Turkana, Volta and Zambezi river basins). The European Commission’s Joint Research Center (JRC) Yearly Water Classification History v1.0 data set was used to identify water bodies in each of the basins. Annual malaria incidence data were obtained from the Malaria Atlas Project (MAP) database for the years 2000, 2005, 2010 and 2015. A total of 4907 small dams and 258 large dams in the four basins, with 14.7million people living close (< 5 km) to their reservoirs in 2015, were analysed. The annual number of malaria cases attributable to dams of either size across the four basins was 0.9–1.7 million depending on the year, of which between 77 and 85% was due to small dams. The majority of these cases occur in areas of stable transmission. Malaria incidence per kilometre of reservoir shoreline varied between years but for small dams was typically 2–7 times greater than that for large dams in the same basin. Between 2000 and 2015, the annual malaria incidence showed a broadly declining trend for both large and small dam reservoirs in areas of stable transmission in all four basins. In conclusion, the malaria impact of dams is far greater than previously recognized. Small and large dams represent hotspots of malaria transmission and, as such, should be a critical focus of future disease control efforts.